Cathorops festae (Boulenger 1898) (Siluriformes; Ariidae), a valid species from Ecuador and Peru - Marceniuk, Alexandre P.; Marchena, José; Betancur-R., Ricardo (Zootaxa, 2016)
Over the past decade, the Sea Catfish (Ariidae) genus Cathorops has been the focus of a major taxonomic review, which has resulted in the revalidation of five synonymized nominal species, and the recognition of seven new species. With 21 valid species, Cathorops is currently the most species-rich genus of Ariidae in the New World. The principal lacuna in the taxonomic knowledge of genus species is the uncertain status of Arius festae Boulenger, 1898, described from Naranjal, in the Guayas River basin of Ecuador. In the present study Cathorops festae is redescribed as a valid species based on morphological and molecular data.